The Effect of Applying Humanistic Learning Theory in Islamic Religious Education on Students' Religious Attitudes - Nurhikmah; Ibnu Imam Al Ayyubi; Ari Limay Trisno Putra; Ma'rifatul Nur Mahmudah; Asa Ismia Bunga Aisyahrani (Al-Bustan: Jurnal Pendidikan Islam, 2025)
This study aims to analyze the influence of the application of humanistic learning theory in Islamic Religious Education learning on the improvement of students' religious attitudes at SMP Negeri 3 Bajeng. The population consists of all students at the school, and the sample comprises 26 randomly selected students. This research adopts a quantitative approach using a survey method and explanatory research design. The sampling technique employed is probability sampling with the simple random sampling method. The instruments used in this study include a student religious attitude questionnaire and a learning evaluation test. The results show that the significance value for the relationship between humanistic learning theory and students' religious attitudes is 0.774 (p > 0.05), with a correlation coefficient of 0.059, indicating a very low relationship. Based on these findings, it is concluded that the application of humanistic learning theory does not have a significant correlation with the improvement of students' religious attitudes. These findings indicate that PAI learning requires a more integrated approach, such as habituation of worship and teacher role modeling, to effectively shape students' religious attitudes.